2010
DOI: 10.1074/jbc.m110.132738
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Roles for Exonuclease 1 and Flap Endonuclease 1 in Maintenance of Triplet Repeats

Abstract: Trinucleotide repeats can form stable secondary structures that promote genomic instability. To determine how such structures are resolved, we have defined biochemical activities of the related RAD2 family nucleases, FEN1 (Flap endonuclease 1) and EXO1 (exonuclease 1), on substrates that recapitulate intermediates in DNA replication. Here, we show that, consistent with its function in lagging strand replication, human (h) FEN1 could cleave 5-flaps bearing structures formed by CTG or CGG repeats, although less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Within this general framework, recognition of simple nicked (or gapped) ends, flaps, and covalently connected flaps (bubbles) or HJs can be accommodated. Accommodation of additional structures in flap regions, such as double-stranded segments, or telomeric G4 DNA (Vallur and Maizels, 2010a, b) will depend both on the distance from the nick or gap junction and potential interactions with other parts of the particular enzyme such as the highly divergent C-terminal domain. The elegant simplicity by which Nature has solved complex topological puzzles in substrate recognition and processing is remarkable.…”
Section: Discussionmentioning
confidence: 99%
“…Within this general framework, recognition of simple nicked (or gapped) ends, flaps, and covalently connected flaps (bubbles) or HJs can be accommodated. Accommodation of additional structures in flap regions, such as double-stranded segments, or telomeric G4 DNA (Vallur and Maizels, 2010a, b) will depend both on the distance from the nick or gap junction and potential interactions with other parts of the particular enzyme such as the highly divergent C-terminal domain. The elegant simplicity by which Nature has solved complex topological puzzles in substrate recognition and processing is remarkable.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies have identified overlapping and distinct roles for EXO-1 and FEN-1 in replication, recombination, repair and maintenance of telomeres [21-22]. FEN-1 cleaves 5′ flaps of the branched DNA structures and possesses double-strand-specific 5′-3′ exonuclease activity [23-25].…”
Section: Introductionmentioning
confidence: 99%
“…Such inhibitory effects have been observed for CTG hairpins and CGG tetraplexes in biochemical studies [45, 49, 64], with the CTG repeat having a stronger inhibitory effect on FEN1 incision than the CGG repeat [64]. Moreover, different trinucleotide repeats can adopt distinct secondary structures that may result in different consequences for the roles of FEN1 in modulating repeat stability [64]. Other factors that could affect FEN1 are the genomic location of the CAG repeat-containing gene and its transcriptional activity.…”
Section: Dual Functions Of Fen1 In Modulating Tnr Stabilitymentioning
confidence: 81%
“…We suggest that the data from these mouse models could indicate that the (CTG) 84 and (CGG) 130 TNR sequences are associated with stable hairpin or tetraplex structures that block FEN1 cleavage activity. Such inhibitory effects have been observed for CTG hairpins and CGG tetraplexes in biochemical studies [45, 49, 64], with the CTG repeat having a stronger inhibitory effect on FEN1 incision than the CGG repeat [64]. Moreover, different trinucleotide repeats can adopt distinct secondary structures that may result in different consequences for the roles of FEN1 in modulating repeat stability [64].…”
Section: Dual Functions Of Fen1 In Modulating Tnr Stabilitymentioning
confidence: 94%
See 1 more Smart Citation